Guest-dependent directional complexation based on triptycene derived oxacalixarene: formation of oriented rotaxanes. Issue 1 (22nd October 2015) - Wang, Han-Xiao; Meng, Zheng; Xiang, Jun-Feng; Xia, Yu-Xiang; Sun, Yihua; Hu, Shu-Zhen; Chen, Hui; Yao, Jiannian; Chen, Chuan-Feng
Abstract : Structural changes in the guest cause inversion of the dominant threading direction in triptycene derived oxacalixarene with different semi-cavities. Abstract : The manipulation of supramolecular devices to carry out sophisticated and programmed tasks is bound up with the spatial allocation of their components, especially the threading direction of the guest, which controls the host–guest orientation in the device. However, insights are needed to probe more possibilities for steering the threading direction. We have developed a new system consisting of a three-dimensional nonsymmetric oxacalixarene (H ) with a fixed comformation and (bi)pyridinium salts (G1–G3 ), in which we found that based on the intrinsic discrepancies between the two semi-cavities ofH, the electron densities of the axles greatly affect the threading direction. This was unequivocally demonstrated by NMR spectra and single crystal structures. With elaborate design, unidirectional threading was achieved, resulting in an oriented rotaxane. Therefore, we describe a new approach in which the threading direction and final orientation may be finely controlled by adjustment of the structure of the guest.